"Scripting" Inhabitations of Unwelcome Guests, Hosts, and Ghosts: Unpacking Elements That Constitute Transgenerational Haunting. (2nd October 2019) - Apprey, Maurice
Abstract: A distinction is made between transgenerational transmission and transgenerational haunting. The former privileges trauma that disables the executive functions of the ego, and the latter focuses on the motivation that underlies the pathway of disturbing ancestral mandates that are implanted, stored, deferred, and transferred. Developmental aspects of the psychology of conception, pregnancy, and delivery align transgenerational haunting to Freud's metapsychology. The praxis of how humans transform the events of history into a represented sense of history is clarified through the three-fold technical strategy of determining the sedimentations of history, the reawakening of history into a representational world, and, through the transference, coming to grips with the patient's unconscious wishes, pleas, and demands in the public space between a clinician and an analysand. In the field of conflict resolution between fractured communities, the reawakening and resubjectivization of communal memory is affirmed as the corollary to individual work in the consulting room. In scripting inhabitants of unwelcome guests, hosts, and ghosts, our sense of time loses its linearity of past, present, and future. Instead, pluperfect and spiral circularity of time is privileged.